2019
DOI: 10.1194/jlr.m092676
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Nudt7 decreases bile acid levels and peroxisomal fatty acid oxidation in the liver

Abstract: Lipid metabolism requires CoA, an essential cofactor found in multiple subcellular compartments, including the peroxisomes. In the liver, CoA levels are dynamically adjusted between the fed and fasted states. Elevated CoA levels in the fasted state are driven by increased synthesis; however, this also correlates with decreased expression of Nudix hydrolase (Nudt)7, the major CoA-degrading enzyme in the liver. Nudt7 resides in the peroxisomes, and we overexpressed this enzyme in mouse livers to determine its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…And a recent study found that sirtuin 5 (SIRT5) functions similarly to mTOR, which shuts down peroxisomal β-oxidation by inhibiting the activity of ACOX1 [114]. Other reports have studied CoA in the process of β-oxidation and found that Nudt7 and Nudt19 in the Nudt superfamily can exert positive effects on CoA substrates in certain metabolic processes to promote the metabolic process [115,116]. With the upsurge of research on noncoding RNAs (ncRNAs), some play positive or inhibitory roles in peroxisomal β-oxidation, such as miR-222, miR-25-3p, circ_0005379, and others [117][118][119][120][121][122], which mainly target the rate-limiting enzyme ACOX1.…”
Section: Othersmentioning
confidence: 99%
“…And a recent study found that sirtuin 5 (SIRT5) functions similarly to mTOR, which shuts down peroxisomal β-oxidation by inhibiting the activity of ACOX1 [114]. Other reports have studied CoA in the process of β-oxidation and found that Nudt7 and Nudt19 in the Nudt superfamily can exert positive effects on CoA substrates in certain metabolic processes to promote the metabolic process [115,116]. With the upsurge of research on noncoding RNAs (ncRNAs), some play positive or inhibitory roles in peroxisomal β-oxidation, such as miR-222, miR-25-3p, circ_0005379, and others [117][118][119][120][121][122], which mainly target the rate-limiting enzyme ACOX1.…”
Section: Othersmentioning
confidence: 99%
“…At the whole tissue level, the concentration of CoA changes with the metabolic state by coordinating synthesis and degradation. In the liver, activation of the biosynthetic pathway drives the increase in CoA that occurs in the transition between the fed and fasted state [11,12]. Conversely, the net decrease in the concentration of hepatic CoA observed upon refeeding after a fast requires both inhibition of de novo CoA synthesis and degradation of the cofactor accumulated in the fasted state.…”
Section: Abstract: Cell Compartmentalization; Coenzyme A; Metabolic Rmentioning
confidence: 99%
“…In the peroxisomes of liver and kidneys, CoA is hydrolyzed to 3 0 ,5 0 -ADP and (acyl-)phosphopantetheine by two Nudix hydrolases, Nudt7 and Nudt19, respectively [13][14][15][16]. Unlike intact CoA, these smaller degradation products can exit the peroxisomes [17]; thus, the activity of Nudt7 and Nudt19 likely plays an important role in the regulation of the peroxisomal CoA pool and, in turn, CoA-dependent peroxisomal metabolism [12,17,18]. Consistent with such a role, the expression of Nudt7 and the activity of Nudt19 are higher in the fed state compared to the fasted state Abbreviations GAPDH, glyceraldehyde-3-phosphate dehydrogenase; mBB, monobromobimane; PMP70, ATP-binding cassette, subfamily D, member 3. and inversely correlate with tissue CoA levels in the liver and kidneys, respectively [13,16,19].…”
Section: Abstract: Cell Compartmentalization; Coenzyme A; Metabolic Rmentioning
confidence: 99%
See 1 more Smart Citation
“…How these degradation products are exported out of peroxisomes is not clear. The importance of NUDT7 in peroxisomal metabolism was shown in metabolomics analysis of mice that overexpress NUDT7 in the liver, which revealed a decrease in peroxisomal beta-oxidation and bile acid biosynthesis rates ( Shumar et al, 2019 ). Nudt19-/- mice showed a 20% increase in CoA in the kidney ( Shumar et al, 2018 ; Figure 1A ).…”
Section: Peroxisomal Solute Exportmentioning
confidence: 99%